Free Floating Right Heart Thrombus Associated with Acute Pulmonary Embolism: An Unsettled Therapeutic Difficulty - Clovis Nkoke; Olivier Faucher; Lise Camus; Laurence Flork (Case Reports in Cardiology)
Free floating right heart thrombus is a rare phenomenon in the context of acute pulmonary embolism and it is associated with a poor outcome. The increased use of echocardiography has led to an increased detection of right heart thrombi. However, optimal management of free floating right heart thrombus remains controversial with no clear consensus. We present the case of a 74-year-old woman who presented to the emergency department with acute onset dyspnea on minimal exertion which had developed over a period of 1 day. A computed tomography of the chest demonstrated massive bilateral proximal pulmonary embolism. A bedside transthoracic echocardiography performed showed a moderately dilated, poorly functioning right ventricle with visible highly mobile serpiginous thrombus moving to and fro across the tricuspid valve. Thrombolytic therapy was immediately initiated with tenecteplase which resulted in excellent results. Although there is no clear consensus for the management of right heart thrombus associated with pulmonary embolism, thrombolysis is readily available and can be effective in carefully selected patients.